2006
DOI: 10.1177/02601079x06001700105
|View full text |Cite
|
Sign up to set email alerts
|

On the Convergence of National Corporate Governance Systems

Abstract: Some scholars have argued that the corporate governance systems of the major economies are likely to converge towards the economically best system at a rapid pace, while others maintain that such convergence will not occur because of a variety of forms of path dependence. In this article we first describe the evolution of the different systems. Then we search for evidence that convergence of corporate governance is correlated with globalisation, i.e. governance systems will converge to a certain degree and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Adapted from Gedajlovic (1993:53-54) The growing economic globalisation (and in particular, the competition for global commerce) has stimulated vigorous debates on the similarities and differences between national corporate governance systems; it has particularly highlighted the emergence of a single 'international best' approach to corporate governance (McCahery and Renneboog 2002). Research evidence as represented in the extant literature on the convergence of national corporate governance systems suggests that the 'international best model' mirrors the shareholder model (Shleifer and Vishny 1997;Hansmann and Kraakman 2001;Braendle and Noll 2006;Goergen, Martynova and Renneboog 2005). Indeed discussants, especially law, finance and economics academics tend to emphasise the superiority of the Anglo-Saxon shareholder oriented corporate governance model (Goergen, Martynova and Renneboog 2005).…”
Section: Figure 1: Shareholder and Stakeholder Perspectives On Corpormentioning
confidence: 99%
See 3 more Smart Citations
“…Adapted from Gedajlovic (1993:53-54) The growing economic globalisation (and in particular, the competition for global commerce) has stimulated vigorous debates on the similarities and differences between national corporate governance systems; it has particularly highlighted the emergence of a single 'international best' approach to corporate governance (McCahery and Renneboog 2002). Research evidence as represented in the extant literature on the convergence of national corporate governance systems suggests that the 'international best model' mirrors the shareholder model (Shleifer and Vishny 1997;Hansmann and Kraakman 2001;Braendle and Noll 2006;Goergen, Martynova and Renneboog 2005). Indeed discussants, especially law, finance and economics academics tend to emphasise the superiority of the Anglo-Saxon shareholder oriented corporate governance model (Goergen, Martynova and Renneboog 2005).…”
Section: Figure 1: Shareholder and Stakeholder Perspectives On Corpormentioning
confidence: 99%
“…For example, Shleifer and Vishny (1997) reported that corporate governance systems in Germany and Japan indicate a trend towards uniformity with the US. It has also been noted that one of the principal factors driving economies towards convergence to the Anglo-Saxon model is the failure of alternative models (Shleifer and Vishny 1997;Braendle and Noll 2006).…”
Section: Figure 1: Shareholder and Stakeholder Perspectives On Corpormentioning
confidence: 99%
See 2 more Smart Citations
“…This result needs to be interpreted from a new angle to explain the causality between business internationalization and management control systems in Russia. As advocated by Cohen and Boyd (2000) and Braendle and Noll (2006), the globalization wave throughout the international community forces companies, especially those active in overseas fund procurement and foreign business development, to adopt an internationally standardized corporate governance system. This trend is also noticeable in Russia, where integration with the world economy is advancing.…”
Section: Among Two Dummy Variables That Capture the Attributes Of Topmentioning
confidence: 99%